2012
DOI: 10.1097/ico.0b013e31823d0412
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Graft Survival in Deep Anterior Lamellar Keratoplasty

Abstract: DALK is a successful form of transplantation in stromal corneal disorders with healthy endothelium, with higher long-term graft survival rates and stable ECD 6 months postoperatively. DALK survival rates do not vary significantly over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 21 publications
1
70
1
2
Order By: Relevance
“…We did assume that in the manual dissection group (Group 2) Dua layer baring was not achieved, but nonetheless we did not observe a significant difference in long-term outcomes between the 2 groups. This is in line with previous papers 28,32,36 but in disagreement with data reported from Han and associates 26 and Al-Torbak and associates. 19 It is worth noticing that this variability could be secondary to different amounts of residual stroma in predescemetic DALK.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…We did assume that in the manual dissection group (Group 2) Dua layer baring was not achieved, but nonetheless we did not observe a significant difference in long-term outcomes between the 2 groups. This is in line with previous papers 28,32,36 but in disagreement with data reported from Han and associates 26 and Al-Torbak and associates. 19 It is worth noticing that this variability could be secondary to different amounts of residual stroma in predescemetic DALK.…”
Section: Discussionsupporting
confidence: 68%
“…The percentage of patients with CDVA > _20/40 was in keeping with previous reports showing similar results after PK (73%-91%) or DALK (72%-92%) in patients with KC. [18][19][20]24,26,[28][29][30][31][32] Both a randomized controlled trial 33 and a report from the American Academy of Ophthalmology 10 concluded that DALK is comparable to PK in terms of CDVA and refractive outcomes. On the contrary, a recent graft registry prospective cohort study has shown PK to be superior to DALK in terms of CDVA and graft survival.…”
Section: Discussionmentioning
confidence: 99%
“…Preserving this layer provides the benefits of less risk of rejection and graft failure, when compared with PK. [11][12][13][14] However, DALK could be less effective than PK in eradicating the infection. Early surgical timing may increase the chances of DALK to be curative, allowing the benefit of better graft survival and visual outcomes.…”
mentioning
confidence: 99%
“…bei Keratokonus oder Hornhaut-Narben) [44]. Da die Operation selbst technisch anspruchsvoll ist und die erfolgreiche Trennung der Descemet-Membran vom Stroma eine Herausforderung darstellt, ist die Zahl der Chirurgen, die in diesen Fällen eine konventionelle pKP durchführen, weiterhin groß [45].…”
Section: Risiken Der Lamellierenden Keratoplastikunclassified